Optimalisasi Penerapan Penyanderaan (Gijzeling) Sebagai Instrumen Penagihan Pajak dalam Masa Pandemi - Kerenhapukh Milka Tarmadi Putri (CV. Syntax Corporation Indonesia, 2022)
State revenue from the tax sector in the APBN always increases every year. Taxes are the backbone of state revenue. As Indonesian citizens, of course we realize how essential tax revenue is with the aim of meeting the needs of the state. The importance of one's obligation to pay taxes has been constitutionally outlined precisely in Article 23A of the 1945 Constitution. By paying taxes, citizens have contributed to realizing the general welfare as the ideals of the state. However, due to the large number of taxpayers who do not have good intentions and do everything they can to avoid paying their tax debts, it is therefore necessary to implement gijzeling (hostage taking) as a last resort in a series of tax collections. The method used in this legal research is a normative juridical legal approach, this approach emphasizes legal science but also looks at the reality that applies in society. Based on the results of the study, there are several obstacles in the implementation of gijzeling, namely starting from inadequate human resources where there are not enough officers to carry out hostage taking (gijzeling). Second, the lack of awareness of every tax insurer to immediately pay off their tax debts, many of the tax bearers do illegal ways to be free from all tax debts. Thus, in order to optimize the application of Gijzeling, it is necessary to apply the precautionary principle to tax bearers who do not have good faith in paying off all their tax arrears and make Gijzeling the last resort in a series of tax collections. Second, there needs to be socialization from hostage agencies regarding the technicalities and benefits of Gijzeling to the community